Pengaruh Modal Insani dan Modal Sosial Terhadap Kinerja UMKM Makanan dan Minuman di Surabaya - Yazied Kamal Fanani; Dhiah Fitrayati (Universitas Negeri Surabaya, 2021)
The current pandemic situation is the main enemy for entrepreneurs. They have to keep running their business in the midst of human restrictions on crowding. Facts on the ground show that food and beverage MSMEs have actually increased, but the increase in the number of MSMEs is not accompanied by an increase in sales turnover. The role of MSME actors is needed to increase sales turnover. Through human capital such as knowledge and experience as well as social capital such as relationships from business actors can improve the performance of MSMEs. The purpose of this study is to analyze the influence of human capital and social capital on the performance of food and beverage SMEs in Surabaya. This type of research uses a quantitative approach, with a total sample of 92 business owners. The results of the study show that human capital and social capital simultaneously have a positive and significant effect on the performance of MSMEs. Partially, human capital has a positive and significant effect on the performance of MSMEs and social capital has a positive and significant effect on the performance of MSMEs